the requirement cancellation of the lease in Islamic law jurisprudence comparative study| موجبات فسخ عقد الإجارة في الشريعة الإسلامية دراسة فقهية مقارنة - Rifqiyati Mas'ud (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
This research discusses about Sharia (Islamic Law) in case of consequences ofthe cancellation of lease contract. TI1e conclusion of this study is that the leasetransaction null and void for several reasons: al-iqalah (cancellation from eitherparty), khiyarat (the bidding), al-'udzr (things that prevent one party caimotcontinue ilie aqd), istihalah tanldz (some reason that caused all the parties caimotcontinue the aqd), istihqaq al- ain al-mustajirah (the leased goods has become theproperty of tenants), one of the parties dies. The ability of the writer how toaescribe the views of senior muslim scholars and t:hier followers such asHanafitic, Malikite, Shafiite, Hanbalite, as well as contemporary scholarsbecome feature of this research. TI1e research refers to the classic and modernbooks, by critical a11alysis reading.